Becoming a journalist : a study into the professional socialisation and training of entry-level journalists at the Cape Argus newspaper - Maughan, Karyn (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2004)
This thesis attempts to examine the construction of 'professionalism' within the newsroom of the Cape Argus, an English-medium newspaper in post-apartheid South Africa. It is a qualitative study which tries to evaluate how a particular mainstream media discourse of 'professionalism' is enacted and struggled over in the attitudes, behaviour and perceptions of entry-level journalists and news managers at the newspaper. It asks what the process of 'becoming a journalist' requires of entry-level journalists in terms of their previous education and personal qualities - and examines the newsroom strategies employed by news managers when entry-level journalists do not meet these particular requirements. This thesis looks at how the pressures of operating a daily English-language commercial newspaper may shape both the 'professional' expectations of news managers and their ability to positively contribute to entry-level journalists' 'newsroom training'. In attempting to examine the nature of journalistic 'professionalism', this study explores the ideology of knowledge construction within mainstream South African media. Operating from a 'radical democratic' perspective of journalism, which prioritises journalism as a vehicle for diverse social, cultural and political expression, this thesis suggests that South African media education needs to enable journalism students' understanding of the ideological construction of journalistic 'professionalism'.
Keywords: Argus (Cape Town, -- South Africa); Journalism -- Study and teaching -- South Africa; Journalists -- Training of -- South Africa; Journalists -- Selection and appointment -- South Africa; Journalists -- Education -- South Africa